Determining the hydrological benefits of clearing invasive alien vegetation on the Agulhas Plain, South Africa - Nowell, Megan Sarah (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.